2000
DOI: 10.1046/j.1469-0691.2000.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibiotic susceptibility of Listeria species: L. grayi, L. innocua, L. ivanovii, L. monocytogenes, L. seeligeri and L. welshimeri strains

Abstract: The present study describes a database on the natural susceptibility of Listeria spp. to a wide range of antibiotics, which can be used to validate susceptibility testing results of these microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
1
19

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 25 publications
11
110
1
19
Order By: Relevance
“…Most Listeria species are susceptible to all antibiotics except cephalosporins and fosfomycin, to which they are naturally resistant [8]. However, increasing reports of Listeria strains isolated from various sources that are resistant to penicillin, ampicillin, tetracycline, streptomycin, clindamycin, and even oxacillin and vancomycin represent a major public health concern [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Most Listeria species are susceptible to all antibiotics except cephalosporins and fosfomycin, to which they are naturally resistant [8]. However, increasing reports of Listeria strains isolated from various sources that are resistant to penicillin, ampicillin, tetracycline, streptomycin, clindamycin, and even oxacillin and vancomycin represent a major public health concern [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As regards L. monocytogenes, the isolates were found resistant to nalidixic acid and ceftriaxone, and partly resistant to clindamycin and cefotaxime. Resistance to "modern" cephalosporins and to nalidixic acid was expected because it is considered an innate resistance (Troxler et al, 2000). In regard to clindamycin, according to Chen et al (2010), its effect to Listeria species is a controversial issue as some studies suggested its sensitivity whereas another study reported high incidence of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Cui et al (2005) synthesized a series of oxazolidinones and compared their activities against a panel of gram-positive bacteria with linezolid. Troxler et al (2000) described a database on susceptibility of Listeria species strains to a wide range of antibiotics. Scortti et al (2006) studied fosfomycin susceptibility against L. monocytogenes and found resistant in vitro, although they are in fact susceptible to the antibiotics during infection.…”
Section: Discussionmentioning
confidence: 99%